Effects of Steaming on the Functional Properties and Mineral Content of Lumi-Lumi Fish (Harpodon Nehereus) Meal - Safrida, Safrida; Rahma, Cukri; Putra, Onetusfifsi; Rinawati, Rinawati; Nurtiana, Winda; Kurniati, Yeni (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2023)
The purpose of this study is to evaluate the mineral content, phenolic content, antioxidant activity, and soluble protein of Lumi-lumi fish meal (Harpodon nehereus) treated with and non-steamed for 30 min. The results revealed that iron (Fe) mineral content was significantly higher in the steamed than non-steamed treatment but not in calcium (Ca). However, there was a decrease in the minerals magnesium (Mg), phosphorus (P), and zinc (Zn) during the steamed process, which was not significant. Then, during steamed, there was a significant decrease in antioxidant activity but not in total soluble protein, whereas phenolic content increased. Based on the findings of this study, Lumi-lumi fish (Harpodon nehereus) meal steamed treatment could be the best treatment because it contained the best phenolic and Fe and Ca minerals.